Studien zum Sexualverhalten and ihr politischer Einfluss - Štulhofer, Aleksandar (Array, 2004)
A short history of sexual risk taking research (SRT) in Croatia and its social impact, particularly in terms of HIV/AIDS prevention campaigns and sex education programs, is presented. The first part of the paper discusses the most important behavioral studies carried out in Croatia during the 1971-2003 period. The analysis points out their theoretical shortcomings and methodological limitations, suggesting steps necessary for improving future research in this area. Underdeveloped interdisciplinary work, it is argued, remains a serious impediment to sexual risk-taking research. The second part of the paper offers a concise analysis of (the lack of) research-related social outcomes. Two cases are presented in more detail: an enigmatic HIV/AIDS public campaign introduced in 1997, and the absence of systematic, school-based sexuality education. In the conclusion, an explanation for the lack of ties between the research and SRT-related health initiatives is presented. It focuses on the interplay between theoretical and methodological shortcomings of the existing body of research and the ideological underpinnings of social reception as the major impediment to a much-needed integration of research and policy-making regarding sexual and reproductive health in Croatia.